2020
DOI: 10.1038/s41438-020-00387-w
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the battle between nectarine and Monilinia laxa: the fruit developmental stage dictates the effectiveness of the host defenses and the pathogen’s infection strategies

Abstract: Infections by the fungus Monilinia laxa, the main cause of brown rot in Europe, result in considerable losses of stone fruit. Herein, we present a comprehensive transcriptomic approach to unravel strategies deployed by nectarine fruit and M. laxa during their interaction. We used M. laxa-inoculated immature and mature fruit, which was resistant and susceptible to brown rot, respectively, to perform a dual RNA-Seq analysis. In immature fruit, host responses, pathogen biomass, and pathogen transcriptional activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…Candidate gene analyses based on the 14 reliable significant QTNs reported in our study are in agreement with differentially expressed genes (DEG) reported by Balsells-Llauradó et al (2020) . Out of 146 candidate genes indicated in brown rot tolerance reported in our study ( Supplementary Table 3 ) 58 were differentially expressed in mature fruit of nectarine cultivar Venus 48 h after inoculation with M. laxa ( Balsells-Llauradó et al, 2020 ). Moreover, out of 25 candidate genes annotated in disease resistance response in our study ( Table 5 ), 8 were also reported by Balsells-Llauradó et al (2020) in mature fruit.…”
Section: Discussionsupporting
confidence: 89%
“…Candidate gene analyses based on the 14 reliable significant QTNs reported in our study are in agreement with differentially expressed genes (DEG) reported by Balsells-Llauradó et al (2020) . Out of 146 candidate genes indicated in brown rot tolerance reported in our study ( Supplementary Table 3 ) 58 were differentially expressed in mature fruit of nectarine cultivar Venus 48 h after inoculation with M. laxa ( Balsells-Llauradó et al, 2020 ). Moreover, out of 25 candidate genes annotated in disease resistance response in our study ( Table 5 ), 8 were also reported by Balsells-Llauradó et al (2020) in mature fruit.…”
Section: Discussionsupporting
confidence: 89%
“…Balsells-Llauradó et al [5] showed that M. laxa inoculation induced the early stage of JA biosynthesis, but a gene downregulation was detected in some cases of ripe fruit inoculated with M. laxa compared to control fruits [5]. The authors concluded that JA activity was likely useful as a plant defense signaling molecule [5]. This was in agreement with our results that MeJA increased the phenolic content, antioxidant capacity, and enzyme activities of fruits inoculated with M. laxa compared to control fruits (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, some fungi can hijack the JA signaling pathway and the pathogen can cause disease [104]. Balsells-Llauradó et al [5] showed that M. laxa inoculation induced the early stage of JA biosynthesis, but a gene downregulation was detected in some cases of ripe fruit inoculated with M. laxa compared to control fruits [5]. The authors concluded that JA activity was likely useful as a plant defense signaling molecule [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations